Oral health assessment in institutionalized elderly: a scoping review - M.H Bakker; M.J de Smit; A. Valentijn; A. Visser (BMC, 2024)
Abstract When elderly become frail and in need for complex care, they can no longer live independently at home and may be admitted to nursing homes. Various studies have shown that oral health in this population is remarkably poor, which may lead to distressing situations and impacts quality of life. A variety of definitions or descriptions for oral health is used. Without a uniform parameter, it is impossible to determine whether oral health in institutionalized elderly is actually improving or deteriorating over time, as well as the effect of (preventive) interventions. In search for an adequate and clinically applicable parameter to determine oral health in this specific patient group, this scoping review aims to give an overview of the currently used parameters for determining oral health in institutionalized elderly. Ninety different parameters were identified, and 50 parameters were solely used by one study. Only 4 parameters were frequently used (in > 20 studies). The relevance of these parameters for this specific patient group is discussed. To aid the planning and commissioning of future research and patient care, there is an urgent need for an adequate and uniform parameter for oral health determination in institutionalized elderly.